The genus Pseudopaguristes McLaughlin (Crustacea: Decapoda: Anomura: Diogenidae) from the southwestern Pacific, with the descriptions of two new species - Rahayu, Dwi Listyo (Zootaxa, 2008)
Two new species of Pseudopaguristes, P. mclaughlinae and P. pachydactylus are described from the southwestern Pacific. Both species have tuberculate spines that cover the mesial faces of the dactyls of the chelipeds, a character shared with P. hians (Henderson, 1888) and P. asper Rahayu, 2005. Pseudopaguristes mclaughlinae n. sp. differs from the two previously mentioned species in having the long and slender pereopods and a tergal thickening of the left second to fourth pleonal somites accompanied by row of long, moderately dense, plumose setae in females. Pseudopaguristes pachydactylus n. sp. is characterized by the short dactyls of the triangularly-shaped chelipeds and the absence of a row of hooked spines on the distal margin of inferior lamella of the male first pleopod. Two other species also found in the region are P. monoporus (Morgan, 1987) and P. laurentae (Morgan & Forest, 1991). A key to the known Indo-Pacific species of the genus Pseudopaguristes is provided.